The effect of Alpinia oxyphylla essential oil on growth performance, immune, antioxidant functions and gut microbiota in pigs - Chen, Fengming; Liu, Zhimou; Xie, Chun; He, Jieyi; Chen, Jiayi; Peng, Kaiqiang; Chen, Xu; He, Jiajia; Liu, Zhenyi; Yang, Hui; Kang, Kelang; He, Binsheng; et al. (Frontiers in Veterinary Science, 2024)
Alpinia oxyphylla, a perennial herb belonging to the Zingiberaceae family, has a long history of traditional medicinal use. The present study evaluated the efficacy of different concentrations of Alpinia oxyphylla essential oil (AEO) on the growth performance, serum antioxidation capacities, immune function, apparent digestibility of nutrients, and gut microbiota in fattening pigs. A total of 120 pigs were divided into five treatments, with six replicates each and four pigs per replicate. The pigs were fed a basal diet or basal diet with chlortetracycline (CTC) alone or AEO at 250, 500, and 1,000 mg/kg (referred to as groups AEO1, AEO2, and AEO3, respectively) for 35 days, preceded by a 7-day pre-feed period. The results show that there were no statistically significant differences in growth performance for any dose of AEO supplementation. AEO increased L-DLC content, total protein content and the activity of GSH in serum (p < 0.05). The AEO also exhibited a linear increase in serum IgG content (p < 0.05). Dietary supplementation with AEO improved apparent digestibility of crude ash and calcium (p < 0.05). In gut microbiota, AEO modified the diversity and abundance of bacterial communities in fattening pigs. The abundance of Dorea, Blautia, Butyricicoccus, Bulleidia, and Lactobacillus was higher in the AEO groups compared to the control group, while Clostridium and Turicibacter were lower. The Bifidobacteriales and Pseudomonas were abundant in group AEO1 and AEO3, respectively. In conclusion, dietary supplementation of 1,000 mg/kg AEO has the potential to improve growth performance, immunological, biochemical, and antioxidant statuses. Additionally, AEO can increase the efficiency of nutrient digestion and absorption through the regulation of gut microbiota.